Blood Glucose Relationship to Fasting Blood Lipids, Acylated Ghrelin, and Response to Carbonated and Flavored Beverage Consumption. (29th May 2020) - Barnett, Joleen; Heying, Emily; Evenson, Alexa; Widmer, Annaliese
Abstract: Objectives: The objective was to 1) determine if carbonation, flavor, and sweetness in beverages impact blood glucose response after consumption and 2) to determine if there is a relationship between fasting glucose concentrations, acylated ghrelin, and blood lipid concentrations. Methods: Participants (males n  = 11, females n  = 14) aged 23–65, BMI < 30 kg/m 2, and no reported chronic disease participated in a single-blinded randomized crossover design. Participants completed six data collections, arriving four hours fasted and consuming one of six different beverages (water, carbonated-no flavor [CNF], carbonated lime flavor [CL], degassed lime flavor [DL], carbonated lime flavor with aspartame [CLS], and degassed lime flavor with aspartame [DLS]). Blood was collected via finger stick at 0 (baseline), followed by beverage consumption, and then collected at 10 and 45 minutes post consumption into EDTA microtainers. A cholestec machine, ELISA assay, and glucometer were used to measure blood lipids, acylated ghrelin, and blood glucose concentrations, respectively. A repeated measures ANOVA was used to determine differences in glucose response. Spearman rank-order correlation coefficients were used to determine the relationships between variables. Results: Blood glucose concentrations did not differ based on beverage, time, or an interaction between the two ( P > 0.05). The average blood glucose concentration among beverage and time points was 96.68 + 7.76 mg/dL (mean ± SD). There was no correlation between fasting blood glucose (0 min), acylated ghrelin, or any blood lipid measurements ( P > 0.05). There was a correlation between LDL and total cholesterol concentrations (r = .780, P = < 0.0001) and between HDL and LDL concentrations (r = –.417, P  = 0.038). Conclusions: HDL and LDL were negatively correlated and LDL and total cholesterol were positively correlated in adults with BMI < 30 kg/m 2 .  Carbonation, flavor, and artificially sweetened beverages have limited impact on blood glucose change after beverage consumption. Funding Sources: This work was funded by the College of Saint Benedict/Saint John's University Faculty Development Grant and CSB/SJU Undergraduate Research Grant.